2018
DOI: 10.1007/s10211-018-0298-3
|View full text |Cite
|
Sign up to set email alerts
|

Captive-born collared peccary (Pecari tajacu, Tayassuidae) fails to discriminate between predator and non-predator models

Abstract: Captive animals may lose the ability to recognize their natural predators, making conservation programs more susceptible to failure if such animals are released into the wild. Collared peccaries are American tayassuids that are vulnerable to local extinction in certain areas, and conservation programs are being conducted. Captive-born peccaries are intended for release into the wild in Minas Gerais state, southeastern Brazil. In this study, we tested the ability of two groups of captive-born collared peccaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
(64 reference statements)
1
13
0
Order By: Relevance
“…Captive cheetah had difficulty differentiating between control and treatment, showing no difference in behavioural response between these cues. One captive individual did distinguish between the con- Faria et al, 2018). One captive cheetah in this study approached the predatory cue and expressed aggressive behaviour towards this "larger predator," suggesting a lack of danger recognition, an inappropriate response that is at least partially the cause of high mortality after many reintroductions (Edwards et al, 2020;Rowell et al, 2020).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Captive cheetah had difficulty differentiating between control and treatment, showing no difference in behavioural response between these cues. One captive individual did distinguish between the con- Faria et al, 2018). One captive cheetah in this study approached the predatory cue and expressed aggressive behaviour towards this "larger predator," suggesting a lack of danger recognition, an inappropriate response that is at least partially the cause of high mortality after many reintroductions (Edwards et al, 2020;Rowell et al, 2020).…”
Section: Discussionmentioning
confidence: 67%
“…Reintroduction efforts are often unsuccessful with captive individuals dying soon after being released into the wild (McPhee & Carlstead, 2010;Smith & Blumstein, 2013). These individuals may fail to recognise and respond to predatory cues, resulting in the performance of maladaptive behaviours such as not seeking refuge from or aggression towards a larger predator (Magno De Faria et al, 2018;McPhee, 2004). Our study showed that when exposed to artificial auditory cues, semi-wild cheetah (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zoo animals may lose the ability to recognize their natural predators if they reside in zoos for several generations, making reintroduction programs potentially less successful. For example, captive-born collared peccary ( Pecari tajacu ) has been shown to fail in discriminating between predator and non-predator models [ 41 ]. Reduced anti-predator behavior may also occur in the wild, depending on suitable environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, captive-born animals may lack the behavioral skills needed to survive after release, such as the ability to find food, shelter, or mates [34,35]. Sometimes captive-born animals cannot identify and respond to their predators [36,37]. Also, behavioral problems, such as the performance of abnormal behaviors may compromise individuals' survival after translocation [38][39][40].…”
Section: Introductionmentioning
confidence: 99%